(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article examines the definitions of the most effective methods and techniques of teaching English for the 6th classes pupils between general education and boarding schools by the example of studying the verb "to have", taking into account their motivation to learn English.